PENGARUH PENGALAMAN KERJA, ETIKA PROFESI, PROFESIONALISME, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT - Ade Eva Nabela, 15.05.52.0307; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2019)
Public Accountants have the obligation to maintain better audit quality. Audit quality is determined by work experience, professional ethics, professionalism and independence. Therefore, this study aims to examine and analyze empirically the effects of work experience, professional ethics, professionalism, and independence on audit quality (Empirical Study of Public Accountants in the City of Semarang). The population used in this study were all KAP auditors in Semarang City. The sampling method used is purposive sampling, which is sampling based on certain criteria. In this study the variables used were audit quality, while the independent variables consisted of work experience, professional ethics, professionalism, and independence. The data analysis technique uses a survey method, which is distributing questionnaires. The results of this study indicate that work experience and independence have no significant positive effect on audit quality. Professional Ethics and Professionalism have a significant positive effect on audit quality.